2018
DOI: 10.2340/00015555-2769
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Stability of the Healthy Human Skin Microbiome Following Dead Sea Climatotherapy

Abstract: Dead Sea climatotherapy (DSC) is a therapeutic modality for a variety of chronic skin conditions, yet there has been scarce research on the relationship between the cutaneous microbiota and disease states in response to DSC. We characterized the skin bacterial and fungal microbiome of healthy volunteers who underwent DSC. Bacterial community diversity remained similar before and after treatment, while fungal diversity was significantly reduced as a result of the treatment. Individuals showed greater inter-indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
4
16
0
1
Order By: Relevance
“…A recent report of ours highlighted the temporal stability of the healthy skin microbiome following DSC (29). In the current study, we observed three bacterial species which were responsive to DSC, including S. epidermidis and M. luteus whose numbers decreased, and S. mitis which increase in relative abundance following DSC.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A recent report of ours highlighted the temporal stability of the healthy skin microbiome following DSC (29). In the current study, we observed three bacterial species which were responsive to DSC, including S. epidermidis and M. luteus whose numbers decreased, and S. mitis which increase in relative abundance following DSC.…”
Section: Discussionsupporting
confidence: 67%
“…1B, (24)) and the concurrent reports that various therapeutic modalities affect the composition of the skin microbiome on AD skin (17,40), we sought to determine whether DSC-induced AD remission would be accompanied by significant microbiome compositional changes. Of note, we previously reported that prolonged UV exposure in the form of DSC does not alter the composition of the skin microbiome in healthy individuals, yet contributed to changes in skin fungal communities (29). Significant temporal changes were observed on lesional and nonlesional sAD skin, yet not so on mAD and healthy skin (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Samples were taken from the antecubital fossa and popliteal fossa on lesional and contralateral nonlesional sites, and DNA extraction and 16S amplicon libraries were prepared, sequenced and processed as previously described. 7 Using SMURF, 5 we identified four unique full-length 16S rRNA S. aureus sequences, or ribotypes, in our cohort (Fig. 1a).…”
mentioning
confidence: 95%
“…Importantly, our cohort consisted of both children and adults with AD. Samples were taken from the antecubital fossa and popliteal fossa on lesional and contralateral nonlesional sites, and DNA extraction and 16S amplicon libraries were prepared, sequenced and processed as previously described …”
mentioning
confidence: 99%
“…DNA was extracted, and 16S rRNA amplicon libraries were prepared, sequenced and analysed as previously described. 3,4 The resulting taxonomic tables were compared with an existing skin microbiome database of a paediatric population with matched Tanner levels, 5 important due to the effects of puberty on skin microbiome composition. 5 Microbial distribution at all three sampled sites was dominated by the phyla Actinobacteria, Firmicutes and Proteobacteria, similar to previous studies by our group 3 and others.…”
mentioning
confidence: 99%